2020
DOI: 10.1016/j.immuni.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factors Are Key Regulators of T Helper 17 Regulatory T Cell Balance in Autoimmunity

Abstract: Appropriate balance of T helper 17 (Th17) and regulatory T (Treg) cells maintains immune tolerance and host defense. Disruption of Th17-Treg cell balance is implicated in a number of immune-mediated diseases, many of which display dysregulation of the insulin-like growth factor (IGF) system. Here, we show that, among effector T cell subsets, Th17 and Treg cells selectively expressed multiple components of the IGF system. Signaling through IGF receptor (IGF1R) activated the protein kinase B-mammalian target of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 137 publications
3
84
2
Order By: Relevance
“…IGF-I is required for brain growth and development, and the lack of IGF-I in knockout mice resulted in reduced brain growth and hypomyelination (6). In addition, IGF-I, as an effector of Th17/ Treg cell balance, induced proinflammatory responses in EAE (13). Therefore, IGF-I is not only considered as a neuroprotective agent but is also discussed concerning health-related fitness in MS patients after aerobic training (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IGF-I is required for brain growth and development, and the lack of IGF-I in knockout mice resulted in reduced brain growth and hypomyelination (6). In addition, IGF-I, as an effector of Th17/ Treg cell balance, induced proinflammatory responses in EAE (13). Therefore, IGF-I is not only considered as a neuroprotective agent but is also discussed concerning health-related fitness in MS patients after aerobic training (19).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent publication has demonstrated that, in fact, IGFs exert proinflammatory responses in EAE. This effect was shown to be dependent on the presence of IGF-I receptor and mediated via the Akt signaling pathway (13). At the cellular level, IGF-I induced the differentiation of T helper 17 (Th17) cells and therefore impacted the Th17 and regulatory T cell (Treg) balance (13), which is required for host defense and adequate immune tolerance.…”
Section: Relevance Of the Insulin-like Growth Factor System For Msmentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse study recently provided evidence for IGF-1-mediated Th17/Treg dysbalance, favoring development of autoimmunity. Mice without the IGF-1 receptor on T cells showed a substantially reduced disease severity in the experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis ( 22 , 23 ). Interestingly, high IGF-1 was demonstrated in labial glands of pSS patients ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors also regulate tissues and could influence MAIT cells. One example is insulin-like growth factor 1 (IGF-1) signaling, which promotes STAT3 signaling and aerobic glycolysis to increase type-17 effector functionality of T H 17 and ILC3 (229). IGFbp4, an important modulator of IGF1 signaling, is enriched in murine RORgt + T H 17, T reg , and ILC3.…”
Section: Neuroendocrine Systemmentioning
confidence: 99%